Patients’ quality of life assessment following treatment of leg length discrepancy in a single center in Riyadh - AlHuzaimi, Fahad S.; Zamzam, Mohamed M.; AlAujan, Abdulrahman; AlDobikhi, Yousef A.; AlKhayyal, Yazeed A.; AlOmar, Mohammed O. (Journal of Musculoskeletal Surgery and Research)
Objectives: Length disparities of children’s limbs might make it difficult for them to engage in social, recreational, and leisure activities. The main goals of surgical treatment of limb length discrepancy (LLD) are to restore limb function and prevent adverse social effects. The aim of this study was to assess the quality of life (QoL) of children who received therapy for limb length discrepancies. Methods: Twenty participants fit the inclusion criteria and completed the validated and translated version of the electronic questionnaire of the brief version of the world health organization questionnaire for QoL assessment the brief version (WHO-QoL-BREF). Answering the questionnaire was administered by an interviewer over the phone. The questionnaire comprised basic patient information and questions regarding the QoL. Results: There were 12 male participants and eight females. The total WHO-QoL BREF score of the participants is 94.15 ± 10.01 (out of 125). The differences between the mean scores of all domains according to participants’ demographic, distortion, and surgical variables were insignificant. Conclusion: Ensuring the QoL and function improvement after treatment of LLD is crucial. More attention must be paid to selecting the appropriate procedure for the suitable patient when treating LLD.